Conjoint Analysis: Consumer Preferences of Natives Chicken in Bukittinggi City - Edwin, Tevina; Hellyward, James; Rastosari, Adisti; Utami, Yolani; Suharto, El Latifa Sri; Novarista, Noni (Andalasian Livestock, 2024)
When purchasing, consumers will prioritize the attributes attached to the product. Research needs to be done to increase consumer buying interest through consumer preference. Especially if it is done in an area with potential but little interest in Kampong chicken meat, this study aims to look at the preferences of Kampong chicken consumers in Bukittinggi City, West Sumatra, Indonesia. The research implementation time was in August 2023. This study's population is Kampong chicken consumers in several wholesale markets in Bukittinggi. For the sample size, 200 respondents had been taken. The variables in this study are a set of attributes of Kampong chicken: price, color, texture, age, gender, chicken meat parts, and chicken skin. The results showed that the highest importance value was at the age attribute of the chicken, which was 19.069, while the lowest value was the price. Based on calculations, it was found that consumers prefer affordable prices to price stabilization. The preferred meat color was meat with a pink color, chewy skin texture, medium size, 4-5 months old, male sex; the most preferred part was the breast, and the chicken was consumed without the skin.